Synthesis of fine chemicals using catalytic nanomaterials: Structure sensitivity - Murzin, Dmitry Yu; Demidova, Yuliya; Hasse, Benjamin; Etzold, Bastian; Simakova, Irina L. (Producing Fuels and Fine Chemicals from Biomass Using Nanomaterials, 2013)
Conventional industrial synthesis methods, i.e., utilization of homogeneous catalysts, stoichiometric oxidants, strong acids and bases as well as metal salts and batch operations are nowadays undergoing a transition toward the use of solid catalysts and continuous processes. The changes are needed to allow sustainable product quality and diminish the so-called E factor (the ratio of waste to product), which is too high for fine chemicals [1], not being in accord with the green chemistry principles [2]. Heterogeneous catalysts are often cheaper than corresponding homogeneous catalysts composed of, for example, complex ligands, allowing, moreover, easy separation and reuse of the catalyst and in many cases also catalyst regeneration.
CRIS-Team Scopus Importer:2023-08-15